How to Run Reflective Practice Groups A Guide for Healthcare Practitioners. - Kurtz, Arabella (Milton : Routledge, 2019)
In How to Run Reflective Practice Groups: A Guide for Healthcare Professionals, Arabella Kurtz explores the use of reflective practice in the modern healthcare context. Responding to the rapidly increasing demand for reflective practice groups in healthcare and drawing on her extensive experience as a facilitator and trainer, Kurtz presents a fully developed, eight-stage model: The Intersubjective Model of Reflective Practice Groups. The book offers a guide to the organisation, structure and delivery of group sessions, with useful suggestions for overcoming commonly-encountered problems and promoting empathic relationships with clients and colleagues. Clearly and accessibly written, using full situational examples for each stage of the presented model, How to Run Reflective Practice Groups offers a comprehensive guide to facilitating reflective practice in healthcare.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Group counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health